Value chain identification, prioritization and actors mapping in Siliana ALL - Dhehibi, Boubaker; Dhraief, Mohamed Zied; Oueslati-Zlaoui, Meriem; Souissi, Asma; Majri, Rihab; Frija, Aymen; Ouerghemmi, Hassen; Alary, Veronique; Ouji, Mourad; Idoudi, Zied; Rudiger, Udo; Rekik, Mourad (International Center for Agricultural Research in the Dry Areas, 2022)
This report summarizes the proceedings of the workshop “Identification and selection of value chains with characteristics eligible for agroecology upgrading in the governorate of Siliana” held in Siliana, Tunisia on December 8th , 2022. The workshop brought together 40 stakeholders from different backgrounds including farmer’s associations and representatives from public institutions. Based on the previous results obtained in the ALL, the objective of the workshop was to identify the value chains present in the region, choosing among them the two that are the most profitable in a participatory approach. Then, in a parallel session, mapping and assessing all relevant actors, diagnosis of the value chains through SWOT analysis and finally a value chain assessment according to agroecological principles.